Burden of cardiovascular diseases in older adults using aged care services. (18th June 2021) - Hsu, Benjumin; Korda, Rosemary; Naganathan, Vasi; Lewis, Peter; Ooi, Sze-Yuan; Brieger, David; Jorm, Louisa
Abstract: Objective: To quantify the burden of cardiovascular diseases (CVD) in older adults using community and residential care services. Methods: The study population comprised people aged 45+ from the 45 and Up Study (2006–09, n = 266, 942) in Australia linked with records for hospital stays, aged care service and deaths for the period 2006–14. Follow-up time for each person was allocated to three categories of service use: no aged care, community care and residential care, with censoring at date of death. We calculated the prevalence at baseline and entry to aged care, and incidence rates for major CVD and six cardiovascular diagnoses, seven cardiovascular interventions (collectively CV interventions), cardiovascular-related intensive care unit stays and cardiovascular death. Results: The prevalence of major CVD at entry into community care and residential care was 41% and 58% respectively. Incidence per 1, 000 person-years of all major CVD hospitalisations and CV interventions, respectively, was 182.8 (95% CI: 180.0-185.8) and 37.0 (95% CI: 35.6–38.4) for people using community care, and 280.7 (95% CI: 272.2–289.4) and 11.7 (95% CI: 9.8–13.9) for people using residential care. Similar trends were observed for each of the CVD diagnoses and interventions. Crude incidence rates for cardiovascular deaths per 1, 000 person-years were 1.4 (95% CI: 1.3–1.5) in no aged care, 13.3 (95% CI: 12.6–14.1) in community care, and 149.7 (95% CI: 144.4–155.2) in residential care. Conclusion: Our findings demonstrate the significant burden of CVD in people using both community-based and residential aged care services and highlights the importance of optimising cardiovascular care for older adults.